High Stress Life Events and Spiritual Development - James, Barry J. (Journal of psychology and theology, 1999)
This study investigated the relationships between the experience of common high stress life events and measures of adult spiritual development. Three hundred thirty-two respondents (116 male and 216 female) aged from 19 to 79 years completed a four-part survey. Intrinsic and extrinsic religiousness were measured using the Intrinsic/Extrinsic-Revised Scale (Gorsuch & MacPherson, 1989), and universalistic spiritual orientation was assessed using a modified version of the Religious Beliefs Inventory (Ring, 1986). The Fowler Scale (Barnes, Doyle, & Johnson, 1989) was used to estimate faith style. Experience of high stress life events was investigated using a life events survey adapted here from several previous studies, including Holmes and Rahe (1967) and Tennant and Andrews (1976). Results support the hypothesis that the experience of a high stress life event is associated with a universalistic spiritual orientation, but not the hypothesis that intrinsic religiousness is related to the experience of such events. The hypothesis that faith stage is associated with the experience of a high stress life event is supported for males only. This study lends support to earlier case-history reports which indicated that spiritual growth can be a constructive consequence of highly stressful life experiences.